Biodegradación del polímero PVC (policloruro de vinilo) a partir de un extracto enzimático crudo proveniente del hongo Aspergillus Niger cultivado en medio sólido de cáscara de papa (2024)
"This project proposes the biodegradation of the polymer polyvinyl chloride (PVC), using a crude enzymatic extract from the fungus Aspergillus niger, which was cultivated in a solid medium of potato peel (Solanum tuberosum L), in order to mitigate the environmental impact generated by two types of urban solid waste (USW): The first correspond to plastics, such as PVC, which is a non-biodegradable polymer whose residence in the earth is more than 400 years and secondly, the agro-industrial waste of potato peel that corresponds to 50% of the USW. Because the potato peel has a high starch content, this serves as a carbon source, giving it the necessary nutrients for A. niger to grow optimally and synthesize the enzymes associated with the degradation of PVC. To carry out this process, potato peel waste (Solanum tuberosum L), of the sabanera and pastusa varieties, was taken as a culture substrate for the fungus, which The enzyme was incubated for 8 days to obtain the enzymatic extract and to subsequently quantify proteins using the Biuret method, whose extract concentration was taken to 75,000 ppm for the extract of the fungus on sabanera potato and 30,000 ppm for the extract obtained with pastusa potato substrate. The enzymatic activity was measured using the Miller technique (DNS Method) and similarly, in order to identify the type of enzymes present in the enzymatic complex, the molecular weights were evaluated using SDS-PAGE polyacrylamide gel electrophoresis, showing that the enzymes present in the extract were: catalases, oxidoreductase, peroxidase, and protease. Finally, 9 of the 20 test tubes were subjected to enzymatic activity for a period of 1 month, to evaluate their degradation using the weight loss technique, whose percentage result is in a range of 0.2 to 0.6% degradation, and the test tubes were characterized by SEM. These results show that PVC, despite being considered "non-biodegradable", contains enzymes produced by microorganisms capable of altering its polymeric structure and thus making it belong to the group of plastics that can be biodegraded by enzymatic action, as is the case of low-density polyethylene, better known as LDPE.